Notifiche
Cancella tutti

Interpretazione di grafici, integrali.

  

1
589

Spiegare e argomentare.

Autore
1 Risposta



2

1 - COS(x) = COS(x)

COS(x) = 1/2---> x = pi/3

Quindi sommo due integrali

COS(x) - (1 - COS(x)) = 2·COS(x) - 1

∫ (2·COS(x) - 1) dx = 2·SIN(x) - x

valutato da x=0 ad x= pi/3

2·SIN(pi/3) - pi/3

2·SIN(0) - 0 = 0

1 - COS(x) - COS(x) = 1 - 2·COS(x)

∫ (1 - 2·COS(x)) dx = x - 2·SIN(x)

valutato da x = pi/3 ad x = pi

pi - 2·SIN(pi)

pi/3 - 2·SIN(pi/3)= pi/3 - √3

pi - (pi/3 - √3) = (2·pi + 3·√3)/3

2·SIN(pi/3) - pi/3 + (2·pi + 3·√3)/3 = pi/3 + 2·√3

 

 

 

 

 



Risposta
SOS Matematica

4.6
SCARICA